2016
DOI: 10.1096/fj.201600501r
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal delivery of thrombospondin‐2 small interfering RNA inhibits the vascular response to injury in a rat carotid balloon angioplasty model

Abstract: In an effort to inhibit the response to vascular injury that leads to intimal hyperplasia, this study investigated the in vivo efficacy of intraluminal delivery of thrombospondin-2 (TSP-2) small interfering RNA (siRNA). Common carotid artery (CCA) balloon angioplasty injury was performed in rats. Immediately after denudation, CCA was transfected intraluminally (15 min) with one of the following: polyethylenimine (PEI)+TSP-2 siRNA, saline, PEI only, or PEI+control siRNA. CCA was analyzed at 24 h or 21 d by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…21 Bodewes et al reported the expression of Tsp2 was significantly increased in rat carotid artery after balloon injury. 9 Recently, Qi et al also stated TSP2 expression was increased in the aortic tissues and plasma of aortic dissection patients. TSP2 was found to be mainly co-localized with α-SMA and slightly with CD31 rather than CD4 or CD68, implicating Tsp2 was mostly from VSMCs, some from ECs, but not from CD4 + TCs or Møs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Bodewes et al reported the expression of Tsp2 was significantly increased in rat carotid artery after balloon injury. 9 Recently, Qi et al also stated TSP2 expression was increased in the aortic tissues and plasma of aortic dissection patients. TSP2 was found to be mainly co-localized with α-SMA and slightly with CD31 rather than CD4 or CD68, implicating Tsp2 was mostly from VSMCs, some from ECs, but not from CD4 + TCs or Møs.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of Tsp1 in mice inhibited neointima formation upon carotid artery ligation via inhibition of Tsp1/integrin β 1/YAP signaling or alleviated the loss of contractile VSMCs phenotype and collagen deposition 21 . Bodewes et al reported the expression of Tsp2 was significantly increased in rat carotid artery after balloon injury 9 . Recently, Qi et al also stated TSP2 expression was increased in the aortic tissues and plasma of aortic dissection patients.…”
Section: Discussionmentioning
confidence: 99%
“…TSP-1, an endogenous protein which is secreted by platelets in response to arterial injury, is the TSP most associated with intimal hyperplasia and arterial remodeling (Adams, 1997). TSP-2 and TSP-5 are molecules that have recently been linked to vascular remodeling and intimal hyperplasia as well; however, little is known regarding the exact role of TSP-2 and TSP-5 in the pathogenesis of intimal hyperplasia (Bodewes et al 2017, Liang et al 2015, Wang et al 2010. The similarity in the chemical structure of TSP-2 to TSP-1 may explain why TSP-1 and TSP-2 may have similar intimal hyperplastic properties (Helkin et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The similarity in the chemical structure of TSP-2 to TSP-1 may explain why TSP-1 and TSP-2 may have similar intimal hyperplastic properties (Helkin et al 2015). In one study, TSP-2 was shown to have a potential role in promoting intimal hyperplasia after arterial injury (Bodewes et al 2017). In contrast, TSP-5 may be protective against intimal hyperplasia and vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation